Matrix metalloproteinase-9, its inhibitor-1 and interleukines in experimental traumatic brain injury - S. V. Ziablitsev; Ya. S. Yuzkiv (Zaporozhye State Medical University, 2016)
Traumatic brain injury (TBI) is accompanied by high rates of morbidity and mortality in both developed and undeveloped countries that makes it one of the most actual medical and social problems. In recent years matrix metalloproteinases are in increasing interest while studying TBI pathogenesis because of their ability to increase permeability of the blood-brain barrier and to cause nervous tissue matrix reorganization. The goal of given study was to investigate the role of matrix metalloproteinase MMP-9 and its inhibitor TIMP-1 in pathogenesis of TBI. Methods: The study was performed on 98 mature white rats. Moderate severity TBI was modeled with one blow on the cranial vault by means of free-falling plummet. Control group included 30 rats. Cytokines (IL-1b, IL-6, IL-8, TNF-a), MMP-9 and TIMP-1 levels were investigated in animals blood by means of ELISA on the 1st, 3rd, 7th, 14th and 21st days after trauma. Results and discussion: MMP-9 levels increased by only 38,2% on the 1st day, but on the 3rd day there was its marked increase to 538%. It is known that metalloproteinases are released from the cells under the influence of various factors, including cytokines. On the 1st day after trauma it was IL-1β which increased by 705% showing the highest rise among other cytokines and exceeding increase in MMP-9 levels. This might indicate regulatory role of IL-1β. A marked increase in MMP-9 levels in its turn led to TIMP-1 activation. Significant increase in TIMP-1 levels was determined on the 3rd day after trauma. On the 7th day there was a critical period with the highest levels of IL-1β (2147,2%), MMP-9 (720,3%) and TIMR-1 (339,3%). Then all research indicators were decreasing with the most pronounced decrease in IL-1β and MMP-9. Conclusion: MMP-9 levels began to increase on the 1st day after trauma due to influence of mainly IL-1β. An abrupt increase in MMP-9 in its turn caused an increase in TIMR-1 levels. Identified changes in IL-1β, ММР-9 and ТІМР-1 levels after TBI indicate complex relationships between cytokines and intercellular matrix reorganization regulators in formation of intercellular cooperation and neuroinflammation development.